PENGEMBANGAN PROFESI GURU MADRASAH SWASTA DI KOTA SERANG - Apud Apud (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
The purpose of this study is to explain the professional development of private madrasah teachers in Serang City focusing on aspects of implementation, problems, and strategic steps. Data was collected through interviews, observations, and documentation which where then analyzed using models from Miles and Huberman through the steps of data collection, data reduction, data presentation, decision making, and verification. The results showed that: Private Madrasas in Serang City had implemented teacher professional development on a still limited scale through KKG, MGMP activities, training, supervision, and monitoring. The problem of teacher professional development can be seen from two factors, namely: supporting factors and inhibiting factors. Supporting factors include the availability of teachers with undergraduate qualifications and spiritual awareness that being a teacher is a calling of soul (religious awareness). While the inhibiting factors are a mismatch between the scientific field and the subjects being taught, limited funds, and access to self-development; Strategic steps in the development of the teaching profession in the form of human resource development plans, empowerment of teacher working groups and subject teacher deliberations, encourage teachers to carry out continuous professional development.